Ojung As A Cultural Tradition of Calling for Rain In Tongas Kulon Village, Probolinggo - Chumairo Chumairo; Sufyanto Sufyanto (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and explain the meaning of communicative messages in the ojung tradition in Tongas Kulon Village, Probolinggo. That the local cultural traditions in Tongas village which are often believed to be a prayer to ask for rain. The ancestral cultural traditions that are still closely believed but cannot be understood in terms of the meaning contained therein. This research method is descriptive qualitative using Symbolic Interactionism approach by George H. Mead, with Snowball Sampling technique was used to determine informants. Data was collected was by means of semi-structured interviews, observation, and documentation, as well as literature review relevant to cultural traditions. The result of this study indicate that the meaning of communicative messages in the ojung tradition in Tongas Kulon Village, Probolinggo by communicating in the form of symbols on devices that have been interpreted, include: (a) a strong and successful personality, (b) purity of heart in oneself each person, (c) human relationship with Nature and God, (d) beauty and honesty. The communicative message conveyed is also an embodiment of prayer to ask for rain, and mercy and to maintain friendship between residents. The moral message contained is that traditions have ancestral cultural values, with people who respect each other’s ancestral culture in the form of their respective beliefs and beliefs about traditions, as well as prayers and hopes that can be answered. And as a forum for closer friendship between people, so as to create a harmonious life among each other.